2003
DOI: 10.1016/s0735-1097(02)02868-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ximelagatran, an oral direct thrombin inhibitor, r-hirudin and enoxaparin on thrombin generation and platelet activation in healthy male subjects

Abstract: Oral administration of the DTI ximelagatran resulted in a rapid inhibition of both thrombin generation and platelet activation in a concentration-dependent manner using a human shed blood model. The inhibition of thrombin generation by 60 mg ximelagatran was comparable to that observed with doses of r-hirudin and enoxaparin demonstrated to be effective for the treatment of acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 17 publications
5
51
0
2
Order By: Relevance
“…It also increased the template bleeding time consistent with several reports on the antihemostatic effects of LMWH. [29][30][31][32][33][34] The bleeding time test, which remains the most reliable global marker of treatment-induced hemostasis impairment, [22][23][24][35][36][37] was therefore used for the safety assessment of PCA treatment infusion in the equiefficacious dose range. While the absence of significant increase in the bleeding time during PCA infusion does not exclude the possibility of bleeding side effects, 38 the direct comparison between LMWH and PCA strongly suggested that the latter was considerably safer.…”
Section: Discussionmentioning
confidence: 99%
“…It also increased the template bleeding time consistent with several reports on the antihemostatic effects of LMWH. [29][30][31][32][33][34] The bleeding time test, which remains the most reliable global marker of treatment-induced hemostasis impairment, [22][23][24][35][36][37] was therefore used for the safety assessment of PCA treatment infusion in the equiefficacious dose range. While the absence of significant increase in the bleeding time during PCA infusion does not exclude the possibility of bleeding side effects, 38 the direct comparison between LMWH and PCA strongly suggested that the latter was considerably safer.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, unlike heparin, DTIs have an antiplatelet effect. 45,46 Their pharmacokinetic profile precludes the need to measure activated clotting times during the procedure or before sheath removal. Additionally, it has been reported that the most commonly used DTI, bivali rudin, is associated with lower frequency of bleeding at the access site (4%) than are UFH or LMWH (plus glycoprotein IIb/IIIa inhibitors; 7%) in patients undergoing PCI (P<.001).…”
Section: Medicationsmentioning
confidence: 99%
“…Авторы мета-анализа подтвердили данные предыдущего ис-следования [8] о том, что применение дабигатрана ас-социируется с увеличением риска сердечно-сосуди-стых осложнений и делают предположение о том, что па-циентам с увеличенным коронарным риском предпоч-тительнее рекомендовать прямые ингибиторы Xа фак-тора свёртывания, чем прямые ингибиторы тромбина. Анализируя механизмы влияния прямых ингибиторов тромбина и прямых ингибиторов Xа фактора свёртывания в отношении развития сердечно-сосудистых осложне-ний по результатам различных исследований, следует учи-тывать, что, несмотря на одинаковое снижение актива-ции тромбоцитов, генерации тромбина [11], эндогенного потенциала тромбина [12] ксимелагатраном и низко-молекулярными гепаринами, время снижения эндо-генного потенциала тромбина было больше для даль-тепарина в сравнении с ксимелагатраном [12]. Напро-тив, в ряде исследований ривароксабан превосходил дальтепарин в отношении генерации тромбина [13] и сни-жал уровень тканевого фактора, вызывающего агрега-цию тромбоцитов [14].…”
Section: прямые ингибиторы тромбинаunclassified